Studi Deskripsi Tantangan dan Strategi Siswa Sekolah Menengah Pertama dalam Memahami Simbol dan Bahasa Indonesia dalam Pembelajaran Matematika - Gunawan, Ahmad Sry Ahrul; Sudiansyah, Sudiansyah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Understanding Indonesian symbols and language in mathematics learning is a significant challenge for junior high school students, especially in regions with local language diversity. This study aims to explore students' challenges and strategies in understanding mathematical symbols as well as the role of teachers in supporting such learning. The research used a descriptive method with a qualitative approach, involving semi-structured interviews with 30 students and 6 teachers, observation of the learning process, as well as documentation analysis of teaching materials, student learning outcomes, and curriculum documents in three different junior high schools in three districts in West Kalimantan Province. The results showed that students understood basic symbols well, but faced difficulties with more abstract symbols. The use of clear Indonesian language helps students understand the symbols, although local language is sometimes a barrier. Student learning strategies, such as group discussions and the use of digital learning media, as well as the teacher's role in providing contextual and visual explanations proved effective. However, the limitations of teaching materials and the lack of variety of text-based problems are the main challenges. This study concludes that learning mathematical symbols requires a holistic approach that includes developing teaching materials, training teachers, and strengthening students' mathematical literacy. Recommendations include the development of self-learning strategies, bilingual approaches and the use of educational technology. The findings are expected to improve the quality of mathematics learning that is more inclusive and effective.